2015
DOI: 10.1080/17445647.2015.1076744
|View full text |Cite
|
Sign up to set email alerts
|

Structural glaciology of Austre Brøggerbreen, northwest Svalbard

Abstract: Structural glaciological maps can be used to study the structural evolution and past dynamics of glaciers. The map described here documents the glacier-wide structural characteristics of Austre Brøggerbreen, a c. 12 km 2 predominantly cold-based valley glacier in northwest Svalbard. The structural map reveals that the glacier is dominated by deep-penetrating fractures that are now relict (crevasse traces). These structures indicate that, despite being relatively inactive at present, the glacier was once much m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
42
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 17 publications
(44 citation statements)
references
References 29 publications
2
42
0
Order By: Relevance
“…Longitudinal features, visible on the surface of the glacier at the southern side (Figure 5(a) and 5(c)), resemble longitudinal foliation reported from many glaciers worldwide (e.g. Goodsell, Hambrey, & Glasser, 2005;Hambrey, 1975;Hambrey et al, 2005;Jennings, Hambrey, Glasser, James, & Hubbard, 2015). These structures can be traced downflow into an ice-cored moraine complex, where they are still detectable as linear structures (Figure 5(b)) on the surface of the moraine.…”
Section: Glacier Surfacementioning
confidence: 77%
“…Longitudinal features, visible on the surface of the glacier at the southern side (Figure 5(a) and 5(c)), resemble longitudinal foliation reported from many glaciers worldwide (e.g. Goodsell, Hambrey, & Glasser, 2005;Hambrey, 1975;Hambrey et al, 2005;Jennings, Hambrey, Glasser, James, & Hubbard, 2015). These structures can be traced downflow into an ice-cored moraine complex, where they are still detectable as linear structures (Figure 5(b)) on the surface of the moraine.…”
Section: Glacier Surfacementioning
confidence: 77%
“…A number of studies have conducted detailed structural surveys of polar and Alpine glaciers (e.g. Goodsell, Hambrey, & Glasser, 2002;Goodsell, Hambrey, Glasser, Nienow, & Mair, 2005;Hambrey & Lawson, 2000;Jennings, Hambrey, Glasser, James, & Hubbard, 2016), but a few have assessed the temporal evolution of glacier structures in response to evolving stress and strain regimes (Glasser & Scambos, 2008;Hambrey et al, 2005;Phillips et al, 2017). This study aims to map brittle and ductile structures originated from the glacier dynamics, by means of the analysis of high-resolution orthophotos, and to describe structural controls of glacier disintegration for a rapidly downwasting Alpine glacier by investigating structure evolution.…”
Section: Introductionmentioning
confidence: 99%
“…Benn et al, 2009;Gulley, 2009;Gulley and Benn, 2007;Hambrey, 1977) were observed, despite continuous scrutiny of the channel boundaries. As Jennings et al (2015) reported from observations of the glacier surface, locally the glacier exhibits a remarkably low density of ice structures likely to influence the drainage system. The elevation of the conduit outlet at the glacier margin remained broadly constant, meaning that only changes in local (reach-scale) base level could have influenced channel adjustment.…”
Section: Overview Of Morphological Channel Changementioning
confidence: 64%
“…The dominant, easternmost flow unit descending from Steenfjellet to the glacier terminus (Fig. 2) is characterised by scarce, spatially restricted relict transverse fracture traces, typically clear ice of a few centimetres in width; active, open crevasses are absent (Jennings et al, 2015). As is common for many small high-latitude valley glaciers, Austre Brøggerbreen's drainage system is predominantly supraglacial, characterised by deeply incised surface streams and a few isolated moulins (Hagen et al, 1991).…”
Section: Austre Brøggerbreenmentioning
confidence: 99%